People Readiness in the Digital Transformation of PT Cahaya Berkah’s Manufacturing - Trisabron; Achmad Fajar Hendarman (CV. Publikasi Indonesia, 2026)
Digital transformation has become essential for manufacturing competitiveness, yet technology adoption alone does not guarantee improvement because workforce readiness influences implementation success. This study examines people readiness for digital manufacturing transformation at PT Cahaya Berkah, focusing on employees’ knowledge, hard skills, soft skills, and attitudes. It aims to identify competency gaps and formulate interventions supporting Energy Management and Overall Equipment Effectiveness Online initiatives. A quantitative descriptive, cross-sectional design was employed, supported by a Focus Group Discussion. Data were collected through a four-point Likert questionnaire distributed to 1,780 shop-floor-related employees across Powder, Liquid, and Semisolid factories, generating 1,608 responses. Data analysis included descriptive statistics, corrected item-total correlation, Cronbach’s alpha, gap analysis, and normalized Human Development Index assessment. The findings show that all questionnaire items were valid and highly reliable. Knowledge recorded the largest gap and was classified as not ready, while hard skills were categorized as ready. Soft skills and attitudes achieved optimal readiness. Major weaknesses concerned Tableau dashboard interpretation, OEE calculation logic, real-time deviation response, digital documentation, sensor calibration, and data-based problem solving. The study concludes that PT Cahaya Berkah requires structured learning, shop-floor coaching, SOP integration, performance reviews, and reinforcement mechanisms to convert positive attitudes into sustainable operational capability.